Elaboração de zoneamento geoambiental para o perímetro urbano de Santa Maria - RS - Dal'Asta, Ana Paula (2009)
Human activities, in their diversity, it impact on the environment, causing profound changes in the natural landscape, which may reflect a framework of environmental degradation and loss of quality of life, especially in urban environments. Therefore, the environmental analysis beyond the limits of understanding of the natural or human framework, but the integration between society and nature, from the understanding of the processes that are triggered in space as a whole, with a view to identifying strengths and weaknesses. To contemplate this prospect, this research aims to environmental characterization of the landscape, through the development of geoenvironmental zoning of the urban area of Santa Maria, Rio Grande do Sul. The urban area, whose boundaries were defined by the municipality, has an area of 13,092 ha and includes the urban areas and the possible development. The research was undertaken with a theoretical framework for systemic analysis, using the landscape as a category of analysis, and methodological tools such as the use of geo, especially of GIS. The treatment methodology is based on the methodological approach developed by LAGEOLAM / UFSM, with some adjustments. The attributes used to geoenvironmental analysis are the climatic characteristics, the geological substrate, hydrology, geomorphology, surface features and the use and occupation soil. The spatial distribution of landscape components, except the weather information, the creation of thematic maps, and further integration, through a representation of synthesis was conducted in Spring 4.3.3 software, which allowed the manipulation of data from different sources. As a final product was established with a hierarchy composed of nine geoenvironmental units; six units and four features, identifying and limiting potential characteristics for each area. In general, the major limitations are associated flood plains Unit Vacacaí Vacacaí Mirim and the steep slopes in the Unit Campestre Menino Deus where the native vegetation has been preserved. The areas of greatest weakness defined by the occurrence of erosion in gullies, are associated with the Units Nova Santa Marta and Passo das Tropas. It is concluded that the development of Geo-environmental zoning, through the integrated study of the landscape, is an important tool in managing the resources of the area.